2016
DOI: 10.1186/s13068-016-0683-y
|View full text |Cite
|
Sign up to set email alerts
|

RNAi downregulation of three key lignin genes in sugarcane improves glucose release without reduction in sugar production

Abstract: BackgroundSugarcane is a subtropical crop that produces large amounts of biomass annually. It is a key agricultural crop in many countries for the production of sugar and other products. Residual bagasse following sucrose extraction is currently underutilized and it has potential as a carbohydrate source for the production of biofuels. As with all lignocellulosic crops, lignin acts as a barrier to accessing the polysaccharides, and as such, is the focus of transgenic efforts. In this study, we used RNAi to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…We have previously published work describing the downregulation of both the F5H and CCoAOMT in sugarcane, with the result being increased glucose release by enzymatic hydrolysis but with no decrease in lignin. In the F5H lines this was attributed to a change in the lignin monomer ratio (Bewg et al 2016) The final gene assessed in our study, C3H, had the highest expression level in Section B, immediately below the most juvenile Section A. C3H catalyzes the second aromatic hydroxylation reaction in the lignin biosynthesis pathway and is an important hub in controlling metabolic flux into G and S lignin monomer synthesis (Barriere et al 2004;Weng & Chapple 2010). CCoAOMT, along with C3H, are hypothesized to be important control points for cell wall lignification by acting as part of the ferulate production pathway (Barriere et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…We have previously published work describing the downregulation of both the F5H and CCoAOMT in sugarcane, with the result being increased glucose release by enzymatic hydrolysis but with no decrease in lignin. In the F5H lines this was attributed to a change in the lignin monomer ratio (Bewg et al 2016) The final gene assessed in our study, C3H, had the highest expression level in Section B, immediately below the most juvenile Section A. C3H catalyzes the second aromatic hydroxylation reaction in the lignin biosynthesis pathway and is an important hub in controlling metabolic flux into G and S lignin monomer synthesis (Barriere et al 2004;Weng & Chapple 2010). CCoAOMT, along with C3H, are hypothesized to be important control points for cell wall lignification by acting as part of the ferulate production pathway (Barriere et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The increased expression of COMT in young tissue in this research may be to ensure S monomer production during the availability of the initial metabolic flux. Previous work has shown that the RNAi suppression of COMT in sugarcane resulted in decreased lignin and altered S:G ratio ( Bewg et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the COMT gene, one line presented lower lignin content and, along with another line, elevated levels of glucose were observed during enzymatic hydrolysis. Two of the improved glucose release lines (F5H‐2 and COMT‐2) also showed reduced S : G ratios …”
Section: Sugarcane Genetic Engineering and Genes Rolementioning
confidence: 99%
“…Two of the improved glucose release lines (F5H-2 and COMT-2) also showed reduced S : G ratios. 43 Research has shown that it is possible to reduce sugarcane lignification successfully through RNA interference, despite its highly complex and polyploid genome. Suppression of COMT expression by 67% to 97% reduced the lignin content by 3.9% to 13.7%, respectively.…”
Section: Sugarcane Genetic Engineering and Genes Rolementioning
confidence: 99%